2022
DOI: 10.3390/atmos13071092
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Meteorological Drivers of the Extreme Precipitation Event and Devastating Floods of Early-February 2021 in Semarang, Central Java, Indonesia

Abstract: Unusually long duration and heavy rainfall from 5 to 6 February 2021 caused widespread and devastating floods in Semarang, Central Java, Indonesia. The heavy rainfall was produced by two mesoscale convective systems (MCSs). The first MCS developed at 13Z on 5 February 2021 over the southern coast of Sumatra and propagated towards Semarang. The second MCS developed over the north coast of Semarang at 18Z on 5 February 2021 and later led to the first peak of precipitation at 21Z on 5 February 2021. These two MCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…We employed a Hybrid Single-Particle Lagrangian Integrated Trajectory Model (HYSPLIT) method to track the origin of moisture and transports responsible for the extreme precipitation event. Furthermore, this study will also explore the underlying dynamics that drive such moisture transport during extreme rainfall events, similar to the previous studies [21,22]. This is the first comprehensive study that applies a Lagrangian moisture analysis to understand the cause of the extreme precipitation event in Indonesia.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…We employed a Hybrid Single-Particle Lagrangian Integrated Trajectory Model (HYSPLIT) method to track the origin of moisture and transports responsible for the extreme precipitation event. Furthermore, this study will also explore the underlying dynamics that drive such moisture transport during extreme rainfall events, similar to the previous studies [21,22]. This is the first comprehensive study that applies a Lagrangian moisture analysis to understand the cause of the extreme precipitation event in Indonesia.…”
Section: Introductionmentioning
confidence: 64%
“…It is shown that within clusters 1-3, moisture arriving toward various release altitudes was dominated from the altitudes lower than 4.5 km. This is expected as the moist or humid air is found much below 5 km under a layer of warmer air in the lower troposphere [39].…”
Section: Dominant Moisture Origin Pathways and Contributionsmentioning
confidence: 78%
See 2 more Smart Citations
“…Rainfall extremes are a major hazard experienced across the country's numerous islands. This can lead to floods and landslides (Hai et al ., 2017; Hermawan et al ., 2022; Purwaningsih et al ., 2022), with devastating impacts on local populations. Convectively coupled Kelvin waves (CCKWs) are tropical weather systems that travel eastward along the equatorial waveguide, organising convection, forming an important mode of equatorial rainfall variability in the MC, and influencing precipitation extremes (van der Linden et al ., 2016; Ferrett et al ., 2020; Lubis and Respati, 2021).…”
Section: Introductionmentioning
confidence: 99%